2018
DOI: 10.1371/journal.pone.0205295
|View full text |Cite
|
Sign up to set email alerts
|

Combining multi-OMICs information to identify key-regulator genes for pleiotropic effect on fertility and production traits in beef cattle

Abstract: The identification of biological processes related to the regulation of complex traits is a difficult task. Commonly, complex traits are regulated through a multitude of genes contributing each to a small part of the total genetic variance. Additionally, some loci can simultaneously regulate several complex traits, a phenomenon defined as pleiotropy. The lack of understanding on the biological processes responsible for the regulation of these traits results in the decrease of selection efficiency and the selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 92 publications
1
25
0
Order By: Relevance
“…After comparing the loci identified in the current study with the 22 previous GWAA, 46 genomic regions were validated (Table 5). These loci were identified both within the Holstein breed [19,33,35,[37][38][39] and among other breeds such as crossbreed Angus [34], Brahman [40], Brangus [40], Jersey [19] and a tropical composite breed [40]. Identifying genomic regions in independent populations and across breeds suggests that these regions are near the causal mutation and have a common function related to fertility in cattle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After comparing the loci identified in the current study with the 22 previous GWAA, 46 genomic regions were validated (Table 5). These loci were identified both within the Holstein breed [19,33,35,[37][38][39] and among other breeds such as crossbreed Angus [34], Brahman [40], Brangus [40], Jersey [19] and a tropical composite breed [40]. Identifying genomic regions in independent populations and across breeds suggests that these regions are near the causal mutation and have a common function related to fertility in cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, loci associated with HCR1 and TBRD were compared to 22 previous studies investigating both dairy and beef cattle fertility. These studies investigated a variety of fertility traits, including: days to first service, non-return rate and calving interval [19,33], pregnancy success at day 28 [34] or day 42 [35], calving to first service [36], conception rates in heifers and in cows [37][38][39], and postpartum anestrous interval [40]. Loci locations were provided based on UMD 3.1 (ftp://ftp.cbcb.umd.edu/pub/data/Bos_taurus/) and ARS-UCD 1.2 (https://www.animalgenome.org/repository/cattle/ UMC_bovine_coordinates/).…”
Section: Genome-wide Association Analysismentioning
confidence: 99%
“…The production of cattle therefore involves GH, TSH, IGF-1, and insulin because they act together on individual animals [7]. Many genes that participate in the process have been identified, such as MYC, PPARG, GSK3B, TG, STAT5b, and IYD [8,9]. However, the growth and development of biological organisms is very complicated, and there are still many genes involved that need to be identified [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…RNA-Seq experiments in livestock studies have identified significant SNPs in candidate genes associated with metabolic pathways that may play a role in the regulation of production traits [4,[8][9][10][11][12]. This has resulted in an improved understanding of the genetic architecture and a reduction in genome complexity of important traits such as feed efficiency, health, fertility, and meat quality traits in beef cattle [4,8,[13][14][15]. More specifically, the study of genetic variants that may serve as markers to select for feed efficiency or residual feed intake (RFI) may help lead to the genetic improvement of feed efficiency and result in economic and environmental benefits for beef production, as feed costs represent approximately 70% of livestock production expenses [16].…”
Section: Introductionmentioning
confidence: 99%